2015
DOI: 10.1016/j.uclim.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to heat waves: Impact of urban expansion scenarios on urban heat island and heat stress in Paris (France)

Abstract: International audienceThe evolution of heat-wave risk in cities is related to regional climate change in interaction with urban heat island. Land planning and urban transport policies, due to their long-lasting impact on city's size and shape, can also have an influence. However, these combined effects are complex and strongly depend on the indicators used to quantify heat-wave risk. With Paris area as a case study and using an interdisciplinary modelling chain, including a socio-economic model of land-use tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(134 citation statements)
references
References 50 publications
6
120
0
8
Order By: Relevance
“…Numerous studies have found that urban sprawl [1,2] (i.e., low density outward expansion of cities) reduces vegetation cover and, thus, contributes to the urban heat island (UHI) effect-a phenomenon where urban areas experience high temperatures compared to their non-urban surroundings. Most of these studies, however, are based on cross-sectional evidence, which means that they investigated the link between land cover type and land surface temperature, based on data from a single point in time to substantiate their claims.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that urban sprawl [1,2] (i.e., low density outward expansion of cities) reduces vegetation cover and, thus, contributes to the urban heat island (UHI) effect-a phenomenon where urban areas experience high temperatures compared to their non-urban surroundings. Most of these studies, however, are based on cross-sectional evidence, which means that they investigated the link between land cover type and land surface temperature, based on data from a single point in time to substantiate their claims.…”
Section: Introductionmentioning
confidence: 99%
“…To represent the atmosphere, the Community Atmosphere Model version 3 (CAM3; [31]) was used. In addition to this, the system components are: the Community Land Surface Model version 3 (CLM3, [32,33]) to represent the surface, the Community Sea Ice Model version 5 (CSIM5, [34]) to represent the sea ice, and the Parallel Ocean Program version 1.4.3 (POP; [35]) to represent the ocean. The standard version of CAM3 is based on a spectral and Eulerian dynamic core with triangular spectral truncation at wave numbers 31, 42 and 85.…”
Section: Numerical Modeling and Configurationmentioning
confidence: 99%
“…Thus, urban areas are usually warmer than nearby rural areas, a phenomenon recognized as the Urban Heat Island (UHI) effect [3,4]. Studies have shown that the environmental impacts of urban areas can extend well beyond administrative boundaries [5,6], and urban heat islands can increase the health risk of vulnerable populations to heat waves [7]. Intensity of the UHI effect depends on many factors, including building density, height, and arrangement; thermal and reflective properties of construction, paving, and roofing materials structures; size and arrangement of green spaces within the city; local and regional wind fields; season and time of year; and recent weather [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the environmental impacts of urban areas can extend well beyond administrative boundaries [5,6], and urban heat islands can increase the health risk of vulnerable populations to heat waves [7]. Intensity of the UHI effect depends on many factors, including building density, height, and arrangement; thermal and reflective properties of construction, paving, and roofing materials structures; size and arrangement of green spaces within the city; local and regional wind fields; season and time of year; and recent weather [7,8]. The UHI has been primarily characterized by near surface air temperature measurements and by remote sensing of the land surface temperature using thermal infrared sensors [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%